Teachers' perspectives on handwriting and collaborative intervention for children with Autistic Spectrum Disorder. Issue 1 (3rd April 2018) - McNamee, Therese; Patton, Sandra
Abstract : Purpose: This study aims to investigate teacher perspectives on teaching handwriting to children with autistic spectrum disorder (ASD) and collaboration with occupational therapists. Design/methodology/approach: A descriptive design was applied. Purpose-designed surveys were distributed to teachers of children with ASD (aged 4-12 years) in the Republic of Ireland. A response rate of 35 per cent (N = 75) was obtained, with 25 responses analysed using descriptive statistics of closed questions and content analysis of open-ended questions. Findings: Of 139 children with ASD, 80 (58 per cent) were reported to have difficulties with handwriting. Teachers reported specific difficulties with pencil grasp, letter formation and task concept among the children with ASD. Fourteen (56 per cent, N = 25) respondents did not give handwriting as homework. Teachers valued occupational therapy advice, individualised programmes and ongoing consultation during implementation. Interest in occupational therapy education regarding handwriting was reported. Practical implications: Occupational therapy collaboration to address handwriting difficulties for children with ASD should include involvement in teacher education, coordination of teacher–parent collaboration and the need for involvement in early intervention provision within an emergent literacy framework. Originality/value: Handwriting development is challenging for children with ASD. There is limited information on teaching or teacher–occupational therapy collaborative practices to address handwriting difficulties of children with ASD.